Preventing suicide with data - Ng, Alvin Lai Oon * (Star Media Group Berhad, 2023)
Yesterday was World Suicide Prevention Day. We have a reason to celebrate in Malaysia as suicide has finally been decriminalized. Nonetheless, much work is needed on suicide prevention. One vital step that must be taken is to reinstate the National Suicide Registry of Malaysia (NSRM). The last time we had such a formal registry was in 2009. It has been discontinued since then.